The Columbia Knight-Bagehot Guide to Economics and Business Journalism - Kluge, Pamela Hollie (Columbia University Press, 1991)
Assists journalists, along with students and of business and public relations, to feel more comfortable with general business practices. Provides guidance on topics such as reading an earnings statement and understanding corporate finance